15.27=0.965*x-3.78(105.3)

Simple and best practice solution for 15.27=0.965*x-3.78(105.3) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 15.27=0.965*x-3.78(105.3) equation:


Simplifying
15.27 = 0.965x + -3.78(105.3)

Multiply -3.78 * 105.3
15.27 = 0.965x + -398.034

Reorder the terms:
15.27 = -398.034 + 0.965x

Solving
15.27 = -398.034 + 0.965x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-0.965x' to each side of the equation.
15.27 + -0.965x = -398.034 + 0.965x + -0.965x

Combine like terms: 0.965x + -0.965x = 0.000
15.27 + -0.965x = -398.034 + 0.000
15.27 + -0.965x = -398.034

Add '-15.27' to each side of the equation.
15.27 + -15.27 + -0.965x = -398.034 + -15.27

Combine like terms: 15.27 + -15.27 = 0.00
0.00 + -0.965x = -398.034 + -15.27
-0.965x = -398.034 + -15.27

Combine like terms: -398.034 + -15.27 = -413.304
-0.965x = -413.304

Divide each side by '-0.965'.
x = 428.2943005

Simplifying
x = 428.2943005

See similar equations:

| -x/14+5=4 | | 2n^2-5v+3=0 | | 9.16-11=24+7.16p | | -x/12+11=18 | | -x/4-1=26 | | -0.75=y+2 | | 46p-14=36 | | -x/4+3=-6 | | x/3-(-7)=29 | | 5x+5=25+3x | | 91/7+7= | | 9m+3=5m-13 | | x/7+7=20 | | 3(x+2)=5(x+1)-(2-1) | | -6(4--t)=12t | | x/3=4((x-30)/5) | | -15(3x+1)-x-14=19-6(2x+9) | | 15.27=0.956x-251.667 | | 3x+8-4x+6-4+12x-5x=28 | | -15x-9=126 | | -15x-9=116 | | 6x-3-3x-12=12x-15x-3 | | -121x+(-12)=230 | | 9ln(6x)=72 | | 7x+2=4x+12+5 | | 15+7x=2x | | 12x-6-x=6-5x-5+15x | | 4x+16+14x+26-15x-30=0 | | 6x+9=11x+-36 | | 3x+-3=x+9 | | 3(x+2)=5(x+1)-(2x-1) | | 1/3r-20=-5 |

Equations solver categories